Building Design Thinking Through Experience:Systematization of a Didactic Sequence for IntroductoryArchitectural Design Teaching - Cárdenas, Gabriel; Rojas, Augusta (Artes: Architecture, Technology and Sustainability, 2026)
Introductory architectural design education requires teaching strategies that foster the development of design thinking from the earliest stages of architectural training. This study systematizes a didactic sequence implemented with first-semester Architecture students through three progressive stages: observation (Three Perspectives), interpretation (Folds), and experimentation (Chalk Laboratory). The research is based on the systematization of teaching experience and adopts a qualitative approach, using students’ physical models, photographic records, and oral presentations of their work as the primary sources of analysis. The findings reveal progression from descriptive representations to well-founded volumetric compositions. The proposed methodological sequence constitutes a transferable pedagogical strategy for developing design thinking in the early stages of architectural education.
Keywords: design thinking; architectural education; design pedagogy; experiential learning; architectural design